Perilaku Seksual Pranikah Anak Jalanan Tahun 2017 - Siti Rahmadani (Quality : Jurnal Kesehatan, 2018)
Street Children are vulnerable groups in carrying out risky behavior and most street children belong to the category of adolescents so that this becomes a very important problem in risky behavior in adolescents.behavior Sexualis a behavior that aims to attract the opposite sex and activity related to sexual relations conducted in an effort to satisfy sexual urges. The general purpose of this study is to find out the personal and environmental factors of street children sexual behavior in 2017. The research design is descriptive quantitative with a cross sectional approach and interviews with street children. This research instrument uses a structured questionnaire in accordance with the variables studied using primary data. The collected data were analyzed by univariate, bivariate and multivariate. Statistical test uses Chi Square test. Location used at the Philosophia Foundation School. The study sample with a total population of street children at the Philosophia Foundation School in 2017. The results showed that there were 2 personal variables related to age factors and knowledge and environmental factors found there was 1 variable pornography exposure to premarital sexual behavior on street children. The most dominant factor influencing environmental factors in terms of exposure to pornographic media with p-value 0,000 with OR 2,654 with premarital sexual behavior on street children. Based on the results of the study, it is recommended to form adolescent care health services to overcome adolescent reproductive health problems and be a reference for deviant adolescents. It is expected that street children will increase promotive and preventive efforts in the form of reproductive health counseling on adolescents and peer group activities for early reproductive health education.